EMPOWERING SUPERVISION : DEVELOPING EDUCATION TOWARDS SUSTAINABLE NATIONAL DEVELOPMENT - Singhasem, Supattra; Niemted, Wuttichai; Choosuwan, Recha (Journal of Educational Review Faculty of Education in MCU, 2025)
This academic article presents the concept and principles of empowering supervision for school administrators to develop education towards sustainable national development. Educational supervision is one of the methods used to enhance teachers in achieving successful teaching and learning outcomes in line with set goals. According to the National Strategy Plan (2018-2030), the aim is to create security, prosperity, and sustainability through development based on the philosophy of sufficiency economy, which focuses on the sustainable growth of the economy while maintaining and rehabilitating natural resources. Human resource development, especially for the youth, is crucial to ensure they possess the quality and vocational skills required to meet the goals. Educational supervision is closely linked to these objectives as it acts as a mechanism for driving education through teachers in educational institutions. Collaboration between supervisors and those being supervised is a cooperative effort aimed at achieving goals. Empowering supervision is a form of collaborative supervision, consisting of 8 processes: 1) creating understanding, 2) delegating authority, 3) building networks, 4) working together, 5) implementing tasks, 6) providing resource support, 7) empowering and boosting morale, and 8) supervision and evaluation. In addition to empowering supervision, this article also discusses the principles and processes of educational supervision, the development of education, and sustainable national development, as a foundation for educational supervision.